Technologies and Challenges in Proteomic Analysis of Protein S-acylation - Zhou, Bo (J Proteomics Bioinform, 2014)
Protein S-acylation (also called palmitoylation) is a pervasive post-translational modification that plays critical roles in regulating protein trafficking, localization, stability, activity, and complex formation. The past decade has witnessed tremendous advances in the study of protein S-acylation, largely owing to the development of novel S-acylproteomics technologies. In this review, we summarize current S-acylproteomics approaches, critically review published S-acylproteomics studies, and envision future directions for the burgeoning S-acylproteomics field. Emerging S-acylproteomics technologies promise to shed new light on this distinct post-translational modification and facilitate the discovery of new disease mechanisms, biomarkers, and therapeutic targets.